Breathing Effect in a Cobalt Phosphonate upon Dehydration/Rehydration: A Single‐Crystal‐to‐Single‐Crystal Study. Issue 48 (21st October 2013) - Zheng, Tao; Clemente‐Juan, Juan M.; Ma, Jing; Dong, Lin; Bao, Song‐Song; Huang, Jian; Coronado, Eugenio; Zheng, Li‐Min
Abstract Two cobalt phosphonates, [Co2(2, 2′‐bpy)2(H2O)(pbtcH)] (1) and [Co2(H2O)(pbtcH)(phen)2] (2; pbtcH5=5‐phosphonatophenyl‐1, 2, 4‐tricarboxylic acid, 2, 2′‐bpy=2, 2′‐bipyridine, phen=1, 10‐phenanthroline), with layer structures are reported. Compound 1 contains O‐C‐O and O‐P‐O bridged tetramers of Co4, which are further connected by pbtcH4− units to form a layer. In compound 2, the cobalt tetramers made up of water‐bridged Co2 dimers and O‐P‐O linkages are connected into a layer by pbtcH4− units. Upon dehydration, compounds 1 and 2 experience single‐crystal‐to‐single‐crystal (SC–SC) structural transformations to form [Co2(2, 2′‐bpy)2(pbtcH)] (1 a) and [Co2(pbtcH)(phen)2] (2 a), respectively. The process is reversible in each case. Notably, a breathing effect is observed for 1, accompanied by pore opening and closing due to the reorientation of the coordinated 2, 2′‐bpy molecules. The transformation was also monitored by in situ IR measurements. Magnetic studies reveal that antiferromagnetic interactions are mediated between the magnetic centers in compounds 1 and 1 a, whereas ferromagnetic interactions are dominant in compound 2.